Cyanotic congenital heart disease - Not always blue to provide a clue: Time to replace cyanosis with arterial desaturation! - Saurabh Kumar Gupta (Wolters Kluwer Medknow Publications, 2022)
Despite right-to-left shunt, not all patients with so-called cyanotic congenital heart disease (CHD) are cyanosed at all times. Moreover, despite undisputed clinical utility, cyanosis is unreliable for the detection of arterial desaturation. Pulse oximetry, on the other hand, provides a much easier, reliable, and accurate method for detecting arterial desaturation. For optimal detection, therefore, it is perhaps sensible to replace cyanosis with pulse oximetry-based detection of arterial desaturation in all cases with suspected CHD.